Outcomes and Associated Complications of Cranioplasty following Craniectomy in Brunei Darussalam - Shie, Caroline S.M.; Antony, Dawn; Thien, Ady (Asian Journal of Neurosurgery, 2022)
Objective Cranioplasty, commonly performed after decompressive craniectomy, is associated with significant complications. We aim to characterize the outcomes and complications post cranioplasty performed in Brunei Darussalam.Methods and Materials We conducted a nationwide retrospective study of the patients who underwent cranioplasty. Patients who underwent cranioplasty by the Neurosurgical Department from January 2014 to June 2019 were included. Patients were excluded if they did not have a minimum of 30-days follow-up or the initial cranioplasty was performed elsewhere. Outcomes including complications post cranioplasty and 30-day and 1-year failure rates were assessed. All statistical analyses were performed with SPSS version 20 (IBM Corporation, Armonk, New York, USA). The χ2 test, Student's t-test, and the Mann–Whitney U test were performed for nominal, normally, and non-normally distributed variables, respectively. Multivariate logistic regression was used to assess predictors for complications and cranioplasty failure.Results Seventy-seven patients with a median age of 48 (interquartile range, 37–61) years were included. Most cranioplasties used autologous bone (70/77, 90.9%). Infection and overall complication rates were 3.9% and 15.6%, respectively. Cranioplasty failure (defined as removal or revision of cranioplasty) rate was 9.1%. Previous cranial site infection post craniectomy was associated with cranioplasty failure (odds ratio: 12.2, 95% confidence interval [1.3, 114.0], p=0.028).Conclusions Cranioplasty is generally associated with significant complications, including reoperation for implant failure. We highlighted that autologous bone cranioplasties can be performed with an acceptable low rate of infection, making it a viable first option for implant material.
Keywords: cranioplasty; complication; failure; autologous bone